No Primeiro Aniversário do MUD
Comunicado do MUD apelando à democratização da sociedade portuguesa, assinado por Afonso Costa, Alberto Candeias, Alberto Dias, Alves Redol, António Lobo Vilela, Armando Adão e Silva, Barbosa de Magalhães, Bento de Jesus Caraça, Demétrio Duarte, Fernando Mayer Garção, Gustavo Soromenho, José Magalhães Godinho, Luciano Serrão Moura, Luís Câmara Reys, Manuel Catarino Duarte, Manuel Mendes, Manuel Alfredo Tito de Morais, por Maria Isabel Aboim Inglês, Mário de Azevedo Gomes, Mário de Lima Alves, MS e Teófilo Carvalho dos Santos.